Infection of Anisakis sp. larvae in some marine fishes from the southern coast of Kulon Progo, Yogyakarta - EKO SETYOBUDI; SOEPARNO SOEPARNO; SENNY HELMIATI (Society for Indonesian Biodiversity, 2011)
Setyobudi E, Soeparno, Helmiati S (2011) Infection of Anisakis sp. larvae in some marine fishes from the southern coast of Kulon Progo, Yogyakarta. Biodiversitas 12: 34-37. The prevalence, intensity and distribution of Anisakis sp. larvae which infected some fishes at the southern coast of Kulon Progo District were investigated. Totally 95 fish specimens were collected during December 2007. Results of the present study indicated that the Anisakis sp. larvae infected various fish species i.e: Trichiurus lepturus, Parupeneus sp., Lutjanusmalabaricus, Terapon jarbua and Caesio sp. Prevalence and mean intensity of infection showed the differences between fish species. The highest mean intensity of infection was found in L. malabaricus (7.71 larvae/infected host) and T. Lepturus (3.18 larvae/infected host), while the lowest intensity of infection was found in Parupeneus sp., T. jarbua and Caesio sp. (1 larvae/infected host). Infected host organs were body cavities (peritoneum), digestive tract, gonads, and liver. Presence of this parasite may be harmful for consumer; however it can be used for several ecological studies as biological tags.Key words: Anisakis sp., infection, southern coast of Kulon Progo District.